ANALISIS PENGARUH GENDER, TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT - Chusnul Chotimah, 13.05.52.0090; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
This study aims to examine and analyze empirically on the influence of gender, pressure of obedience, task complexity, and experience of auditors on audit judgment at auditors KAP Semarang, Solo and Yogyakarta. The population used in this study are all auditors KAP Semarang, Solo and Yogyakarta. The sampling method used is convenience sampling, which is sample selection based on convenience, so the author has the freedom to choose the most rapid and easy sample. In this study, the dependent variable used is audit judgment, while the independent variable consists of gender, pressure of obedience, task complexity, and experience of the auditor. Data analysis technique using multiple linear regression analysis. The results showed that gender has a positive and significant impact on audit judgment. The pressure of obedience has a positive and significant impact on audit judgment. The complexity of duties has a positive and significant impact on audit judgment. The experience of auditors has a positive and significant impact on audit judgment.Keywords: Gender, Pressure of Obedience, Task Complexity, Auditor Experience and Audit Judgment